Examination of the factorial model of a scale developed to assess body satisfaction in the Brazilian context: a study with people 18 to 40 years old - Silva, Wanderson Roberto Da (2021)
Purpose Confirmatory factor analysis was employed to investigate an instrument developed to assess body satisfaction of Brazilian women and men and to identify participants’ body satisfaction level. Methods Brazilian young adults completed the Body Satisfaction Situational Scale and a sociodemographic questionnaire. A total of 1481 individuals (female = 1035; male = 446) aged between 18 and 40 years old participated in the study. Factorial, convergent and discriminant validity and reliability were evaluated. An invariance test was performed across sexes using multi-group analysis. The prevalence of body satisfaction among participants was calculated using the final models of the instrument. Results The complete model of the scale (23 items and four factors) was invariant across sexes, but it did not fit the samples even after refinement. Therefore, a theoretical investigation of the scale content was performed based on literature. Thus, a reduced model composed of two factors and ten items was found for each sex. These models showed good validity and reliability to independent samples. About prevalence, most of the women were not at all satisfied with body fat and most of the men were slightly satisfied with body musculature. Further, women and men were moderately satisfied with their face, hair, and skin. Conclusion A reduced model of the instrument for women and another for men showed adequate indices of construct validity and reliability to samples. The most participants were not very satisfied with their bodies. The results can be useful to develop protocols aiming to promote body satisfaction. Level of evidence Level V, descriptive cross-sectional study.